Ethics briefing - Norcliffe-Brown, Dominic (Journal of medical ethics, 2021)
During the first UK wave of the pandemic, there were two areas of immediate ethical concern for the medical profession. The first was the possibility that life-saving resources could be overwhelmed. Early reports from hospitals in the Italian city of Bergamo suggested that ventilatory support might need rationing and emergency ‘battlefield’ triage was a real possibility.1 In the UK, several professional bodies, including the British Medical Association and the Royal College of Physicians rapidly developed guidance for doctors should triage become a reality.2 The second issue was the acute shortage of personal protective equipment (PPE). Where doctors were unable to protect their patients - and themselves - from the risk of COVID-19, ethical challenges emerged. Ordinarily, doctors and patients do not present risks of significant harm to each other. To shift to a position where every patient - and every health professional - could potentially be a threat presented serious clinical and ethical challenges. To treat with inadequate PPE, so options for mitigating harms are radically reduced, deepens the challenges. Among the questions the BMA wrestled with was the extent of doctors’ duties to treat infected or potentially infected patients in the absence of effective PPE. The BMA was clear that despite obligations to treat, medicine is not a self-sacrificing profession: there were limits to the risk doctors could be required to expose themselves to.3 These issues no longer seem so pressing. In the UK at least, there is adequate PPE and with the second steep wave behind us, and significant numbers vaccinated, it is less likely that triage will be required in the UK. But as those concerns have receded so other ethical questions have arisen. Among them is a cluster of issues associated with what might be called COVID-19’s indirect harms. Understandably, in response to …